Characterization of barium titanate: BaTiO3 (BT) ceramics prepared from sol-gel derived BT powders - Deshpande, S. B.; Godbole, P. D.; Khollam, Y. B.; Potdar, H. S. (Journal of Electroceramics, 2005)
Sol-gel synthesis was attempted at room temperature by adding drop wise a clear solution (made by reacting BaCO3 with glacial acetic acid) to an equi-molar solution of titanium tetrabutoxide in isopropanol (IPA) and acetic acid. The gelation occurred within 30 minutes. The as-dried gel was calcined at 750 degrees C/6 h in air to obtain carbon free BaTiO3 powders. The resulting BT powders were further pressed into pellets and sintered at 1280 degrees C/4 h in air to get dense ceramics (density similar to 94%). XRD and SEM techniques were used for phase and microstructure analysis respectively. The room temperature relative permittivity (e) of 1280 increased to 7200 (at Curie temperature of 127 degrees C) at 1 kHz frequency. The dissipation factor (tan delta) similar to 1.6% was observed in these samples. Also, the ferroelectric properties such as spontaneous polarization (Ps similar to 13 mu C/cm(2)), coercive field (E-c similar to 4.0 kV/cm) and dielectric strength (similar to 34 kV/cm) are estimated for these samples. These performance parameters are compared with the available standard data from the literature.
Keywords: barium titanate; ferroelectricity; Microstructure; relative permittivity; sol-gel processing

Co-precipitation method for the preparation of nanocrystalline ferroelectric SrBi2Nb2O9 ceramics - Gaikwad, S. P.; Dhage, S. R.; Potdar, H. S.; Samuel, V.; Ravi, V. (Journal of Electroceramics, 2005)
A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase SrBi2Nb2O9. Ammonium hydroxide and ammonium oxalate were used to precipitate Sr2+, Bi3+ and Nb5+ cations simultaneously. No pyrochlore phase was found while heating powder at 850 C and pure SrBi2Nb2O9 (SBN) phase was formed as revealed by the X-ray diffraction (XRD) studies. Particle size and morphology was studied by transmission electron microscopy (TEM). The room temperature dielectric constant at 1 kHz is 100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Chemical synthesis; electronic materials; ferroelectricity; Oxides

Preparation of ferroelectric BaNb2O6 the urea method - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A precipitate was formed when an aqueous solution of BaCl2, NbF5 and urea in required ratio (the ratio of total metal cations to the urea is five) is heated on a water bath at 100 degrees C. This precipitate on decomposition at 600 degrees C yielded the nanocrystallites of BaNb2O6 (BN), as confirmed by X-ray diffraction study (XRD). This is a much lower temperature as compared to that prepared by traditional solid state method (1000 degrees C) as reported for the formation of BaNb2O6. Transmission electron microscope (TEM) investigations revealed that the average particle size is 85 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 900. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides

Preparation of nanocrystalline ferroelectric BaNb(2)O6 by citrate gel method - Gaikwad, S. P.; Samuel, V; Pasricha, R; Ravi, V (Bulletin of Materials Science, 2005)
A gel was formed when a aqueous solution of BaCl2, NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600 degrees C yielded the nano crystallites of BaNb2O6, as confirmed by X-ray diffraction study (XRD). This is a much lower temperature as compared to that prepared by traditional solid state method (1000 degrees C) as reported for the formation of BaNb2O6. Transmission electron microscopic. (TEM) investigations revealed that the average particle size is 50 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1000. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides

Synthesis of bismuth titanate by the urea method - Anilkumar, Mettu; Dhage, S. R.; Ravi, V. (Materials Letters, 2005)
A simple urea precipitation route was adopted for the preparation of bismuth titanate (Bi4Ti3O12) powders. Stoichiometric quantities of BiCl3 and TiOCl2 were mixed with the required amount of urea (the ratio of total metal cations to urea is five), and the mixture was heated on a water bath. This leads to the formation of precipitate, which was decomposed at 973 K. The formation of bismuth titanate was observed on calcining powders at 973 K by X-ray diffraction studies. The average particle size is found to be 100 nm by microscopy. The room temperature dielectric constant is found to be 150 at 1 kHz. The hysteresis loop parameters were also obtained by home-built Sawer-Tower circuit. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; dielectric properties; ferroelectricity; X-ray diffraction

Synthesis of Sr0.5Ba0.5Nb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Chemistry and Physics, 2005)
A gel was formed when an aqueous solution of BaCl2, SrCl2, NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at I kHz is 1000. The ferroelectric hysteresis loop parameters of these samples were also studied by a home built Sawyer-Tower circuit. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides

Synthesis of Sr0.5Ba0.5Nb2O6 by urea method - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A precipitate was formed when an aqueous solution of SrCl2, BaCl2, NbF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath.. This precipitate on decomposition at 750 degreesC yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). This is much lower temperature as compared to that prepared by traditional solid state method (1000 degreesC as reported for the formation of SBN ceramics. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1050. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides

Co-precipitation technique for the preparation of ferroelectric BaBi2Ta2O9 - Dhage, S. R.; Pasricha, R.; Murugan, A. Vadivel; Ravi, V. (Materials Chemistry and Physics, 2006)
A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase BaBi2Ta2O9 (BBT). Ammonium hydroxide and ammonium oxalate were used to precipitate Ba2+, Bi3+ and Ta5+ cations simultaneously. No pyrochlore phase was found while heating powder at 800 degrees C and pure BaBi2Ta2O9 phase was found to be formed by X-ray diffraction. Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 350. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides

Coprecipitation technique to prepare Sr0.5Ba0.5Nb2O6 - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Bulletin of Materials Science, 2006)
An aqueous mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and strontium ions as oxalates and niobium ions as hydroxide under basic conditions. This precursor on calcining at 750 degrees C yielded Sr0.5Ba0.5Nb2O6 phase. This is a much lower temperature than that prepared by traditional solid state method (1000 degrees C) as reported for the formation of Sr0.5Ba0.5Nb2O6 (SBN). Transmission electron microscopic (TEM) investigations revealed that the average particle size was 80 nm for the calcined powders. The room temperature dielectric constant at I kHz was found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides; X-ray diffraction

Flexible composite mechanical energy harvester from a ferroelectric organoamino phosphonium salt - Vijayakanth, Thangavel; Srivastava, Anant Kumar; Ram, Farsa; Kulkarni, Priyangi; Shanmuganathan, Kadhiravan; Praveenkumar, Balu; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2018)
A new binary organic salt diphenyl diisopropylamino phosphonium hexaflurophosphate (DPDPPF6) was shown to exhibit a good ferroelectric response and employed for mechanical energy harvesting application. The phosphonium salt crystallizes in the monoclinic noncentrosymmetric space group Cc and exhibits an H-bonded 1D chain structure due to N-HF interactions. Ferroelectric measurements on the single crystals of DPDPPF6 gave a well-saturated rectangular hysteresis loop with a remnant (P-r) polarization value of 6Ccm(-2). Further, composite devices based on polydimethylsiloxane (PDMS) films for various weight percentages (3, 5, 7, 10 and 20wt%) of DPDPPF6 were prepared and examined for power generation by using an impact test setup. A maximum output peak-to-peak voltage (V-PP) of 8.5V and an output peak-to-peak current (I-PP) of 0.5A was obtained for the non-poled composite film with 10wt% of DPDPPF6. These results show the efficacy of organic ferroelectric substances as potential micropower generators.
Keywords: binary phosphonium salts; energy conversion; ferroelectricity; hydrogen bonding; polymer composites

Flexible energy harvester from an organic ferroelectric ammonium salt - Gupta, Rishabh; Sahoo, Supriya; Deswal, Swati; Kothavade, Premkumar; Dixit, Prashant; Zareba, Jan K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Chemistry-An Asian Journal, 2021)
Organic ferroelectrics due to their low cost, easy preparation, light weight, high flexibility and phase stability are gaining tremendous attention in the field of portable electronics. In this work, we report the synthesis, structure and ferroelectric behavior of a two-component ammonium salt 2, containing a bulky [Bn(4-BrBn)NMe2](+) (Bn=benzyl and 4-BrBn=4-bromobenzyl) cation and tetrahedral (BF4)(-) anion. The structural analysis revealed the presence of rich non-classical C-H...F and C-H...Br interactions in this molecule that were quantified by Hirshfeld surface analysis. The polarization (P) vs. electric field (E) hysteresis loop measurements on 2 gave a remnant polarization (P-r) of 14.4 mu C cm(-2) at room temperature. Flexible polymer composites with various (5, 10, 15 and 20) weight percentages (wt%) of 2 in thermoplastic polyurethane (TPU) were prepared and tested for mechanical energy harvesting applications. A notable peak-to-peak output voltage of 20 V, maximum current density of 1.1 mu A cm(-2) and power density of 21.1 mu W cm(-2) were recorded for the 15 wt% 2-TPU composite device. Furthermore, the voltage output generated from this device was utilized to rapidly charge a 100 mu F capacitor, with stored energies and measured charges of 156 mu J and 121.6 mu C, respectively.
Keywords: Dielectric; energy harvesting; ferroelectricity; organic composites; piezoelectric

Highly electrostrictive salt cocrystal and the piezoelectric nanogenerator application of its 3D-printed polymer composite - Sahoo, Supriya; Panday, Rishukumar; Kothavade, Premkumar; Sharma, Vijay Bhan; Sowmiyanarayanan, Anirudh; Praveenkumar, Balu; Zareba, Jan K.; Kabra, Dinesh; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (ACS Applied Materials and Interfaces, 2024)
Ionic cocrystals with hydrogen bonding can form exciting materials with enhanced optical and electronic properties. We present a highly moisture-stable ammonium salt cocrystal [CH3C6H4CH(CH3)NH2][CH3C6H4CH(CH3)NH3][PF6] ((p-TEA)(p-TEAH)PF6) crystallizing in the polar monoclinic C2 space group. The asymmetry in (p-TEA)(p-TEAH)PF6 was induced by its chiral substituents, while the polar order and structural stability were achieved by using the octahedral PF6- anion and the consequent formation of salt cocrystal. The ferroelectric properties of (p-TEA)(p-TEAH)PF6 were confirmed through P-E loop measurements. Piezoresponse force microscopy (PFM) enabled the visualization of its domain structure with characteristic ``butterfly'' and hysteresis loops associated with ferro- and piezoelectric properties. Notably, (p-TEA)(p-TEAH)PF6 exhibits a large electrostrictive coefficient (Q(33)) value of 2.02 m(4) C-2, higher than those found for ceramic-based materials and comparable to that of polyvinylidene difluoride. Furthermore, the composite films of (p-TEA)(p-TEAH)PF6 with polycaprolactone (PCL) polymer and its gyroid-shaped 3D-printed composite scaled-up device, 3DP-Gy, were prepared and evaluated for piezoelectric energy-harvesting functionality. A high output voltage of 22.8 V and a power density of 118.5 mu W cm(-3) have been recorded for the 3DP-Gy device. Remarkably, no loss in voltage outputs was observed for the (p-TEA)(p-TEAH)PF6 devices even after exposure to 99% relative humidity, showcasing their utility under extremely humid conditions.
Keywords: 3D printing; cocrystals; energy harvesting; ferroelectricity; Piezoelectricity